Sustainable greenhouse policies: The role of non-CO 2 gases - Peter Michaelis (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper investigates the economic implications of a comprehensive approach to sustainable greenhouse policies that strives to stabilise the atmospheric concentration of the five major greenhouse gases at an ecologically determined threshold level. In a theoretical optimisation model conditions for an efficient allocation of abatement effort among pollutants and over time are derived. The model is empirically specified and adapted to a dynamic GAMS-algorithm. By various simulations run for a time period of 200 years (1990 to 2190), the economics of greenhouse gas accumulation are explored. In particular, the long-run costs associated with the above stabilisation target are evaluated for two different policy scenarios: a comprehensive approach that covers all major greenhouse gases simultaneously and a "piecemeal approach" that is limited to reducing CO2 or a selected subset of greenhouse gases, respectively. By comparing the simulation results, the potential losses in efficiency associated with a piecemeal approach are evaluated, and some policy implications are discussed.
Keywords: Q20; 330; Climate change; Sustainable development; Environmental policy; Umweltpolitik; Luftverschmutzung; Klimawandel; Nachhaltige Entwicklung; Theorie